Contracting amounting to less than or equal to 8 tax units (UIT) and its impact on the Municipal Management of Chorrillos - Marchini Pardo, Fiorella Sabina (2025)
The paper aimed to determine the impact of contracting up to 8 UIT on the municipal management of the Chorrillos district during 2022, using a quantitative non-experimental, correlational, and cross-sectional design approach. The sample, selected by convenience, made up of 70 collaborators from various organic units and hierarchical levels involved: Logistics Sub-Management (22), Accounting Sub-Management (18), Treasury Sub-Management (15), Administration and Finance Management (10), and Institutional Control Body (5). The survey technique was applied, and a structured questionnaire with 25 questions on a Likert scale was used as an instrument for data collection. The content validity of the instrument was subject to the judgment of three experts, complemented by the construct validity through Bartlett’s and Kaiser-Meyer-Olkin’s sphericity factor analysis, obtaining optimal results. Furthermore, reliability was confirmed using Cronbach’s alpha test (α=0.844), which indicates high internal consistency. Hypotheses were tested using Spearman’s correlation, finding a positive and strong Rho = 0.759, p < 0.05 between the variables. The results demonstrate that this type of contract has a direct impact on municipal management in Chorrillos, as evidenced by budget execution and internal control. Furthermore, the need to implement an internal policy to optimize the process of these contracts is highlighted, along with other mechanisms, such as the creation of an internal control committee and the delegation of functions, in order to improve institutional efficiency and its public perception.